On the Nonexistence of Market Equilibria in Exhaustible Resource Markets with Decreasing Costs - Eswaran, Mukesh; Lewis, Tracy R.; Heaps, Terry (Journal of Political Economy, 1983)
This paper examines the existence of competitive equilibria in markets for exhaustible resources where there are initial economies of scale in either the extraction of the resource or the utilization of the resource as an input in production. In such instances, which are fairly common, we find that the classic Hotelling rule for competitive extraction does not apply, since competitive price equilibria generally do not exist. This is in marked contrast to static markets where the usual textbook example of firms with U-shaped average cost curves is not inconsistent with the existence of competitive equilibria. Furthermore, oligopolistic market equilibria in which resource firms act as Nash producers may also fail to exist when there are returns to scale in production.